Graded Otx2 activities demonstrate dose-sensitive eye and retina phenotypes. (13th November 2013) - Bernard, Clémence; Kim, Hyoung-Tai; Torero Ibad, Raoul; Lee, Eun Jung; Simonutti, Manuel; Picaud, Serge; Acampora, Dario; Simeone, Antonio; Di Nardo, Ariel A.; Prochiantz, Alain; Moya, Kenneth L.; Kim, Jin Woo
Abstract: In the human, mutations of OTX2 ( Orthodenticle homeobox 2 transcription factor) translate into eye malformations of variable expressivity (even between the two eyes of the same individual) and incomplete penetrance, suggesting the existence of subtle thresholds in OTX2 activity. We have addressed this issue by analyzing retinal structure and function in six mutant mice with graded Otx2 activity: Otx2 +/+, Otx2 +/AA, Otx2 +/GFP, Otx2 AA/AA, Otx2 AA/GFP and Otx2 GFP/GFP . Null mice ( Otx2 GFP/GFP ) fail to develop the head and are embryonic lethal, and compound heterozygous Otx2 AA/GFP mice show a truncated head and die at birth. All other genotypes develop until adulthood. We analyzed eye structure and visual physiology in the genotypes that develop until adulthood and report that phenotype severity parallels Otx2 activity. Otx2 +/AA are only mildly affected whereas Otx2 +/GFP are more affected than Otx2 +/AA but less than Otx2 AA/AA mice. Otx2 AA/AA mice later manifest the most severe defects, with variable expressivity. Electrophysiological and histological analyses of the mouse retina revealed progressive death of bipolar cells and cone photoreceptors that is both Otx2 activity- and age-dependent with the same ranking of phenotypic severity. This study demonstrates the importance of gene dosage in the development of age-dependent pathologies and underscores the fact that small gene dosage differences can cause significant pathological states.